Crosstalk between the mesothelium and lymphomatous cells: insight into the mechanisms involved in the progression of body cavity lymphomas. (19th November 2013) - Lignitto, Laura; Mattiolo, Adriana; Negri, Elena; Persano, Luca; Gianesello, Lisa; Chieco‐Bianchi, Luigi; Calabrò, Maria Luisa
Abstract The peculiar localization of body cavity lymphomas implies a specific contribution of the intracavitary microenvironment to the pathogenesis of these tumors. In this study, primary effusion lymphoma (PEL) was used as a model of body cavity lymphoma to investigate the role of mesothelial cells, which line the serous cavities, in lymphoma progression. The crosstalk between mesothelial and lymphomatous cells was studied in cocultures of primary human mesothelial cells (HMC) with PEL cells and a xenograft mouse model of peritoneal PEL. PEL cells were found to induce type 2 epithelial–mesenchymal transition (EMT) in HMC, which converted into a myofibroblastic phenotype characterized by loss of epithelial markers (pan cytokeratin and E‐cadherin), expression of EMT‐associated transcriptional repressors (Snail1, Slug, Zeb1, Sip1), and acquisition of α‐smooth muscle actin (α‐SMA), a mesenchymal protein. A progressive thickening of serosal membranes was observed in vivo, accompanied by loss of cytokeratin staining and appearance of α‐SMA‐expressing cells, confirming that fibrosis occurred during intracavitary PEL development. On the other hand, HMC were found to modulate PEL cell turnover in vitro, increasing their resistance to apoptosis and proliferation. This supportive activity on PEL cells was retained after transdifferentiation, and was impaired by interferon‐α2b treatment. On the whole, our results indicate that PEL cells induce type 2 EMT in HMC, which support PEL cell growth and survival, providing a milieu favorable to lymphoma progression. Our findings provide new clues into the mechanisms involved in lymphoma progression and may indicate new targets for effective treatment of malignant effusions growing in body cavities.